1982
DOI: 10.1002/j.1551-8833.1982.tb05016.x
|View full text |Cite
|
Sign up to set email alerts
|

Organizing and analyzing leak and break data for making main replacement decisions

Abstract: Water main replacement decisions may be based on arbitrary criteria such as age or on historic operating records and the experiences of a utility. Use of the latter method enables a utility to analyze leak and break patterns and to develop rehabilitation‐replacement plans. The author provides an overview of the causes of water main breaks and leaks and then describes several studies in which water main breaks have been analyzed in terms of pipe age, geographic location, or diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 4 publications
2
26
0
2
Order By: Relevance
“…This inconsistency often leads to large variances in reported break rates amongst utilities. For example, O'Day (1982) reported that some systems such as New York City report only main breaks whereas as others such as Houston report both breaks and leaks.…”
Section: Distinction Between Pipe Breaks and Leaksmentioning
confidence: 99%
See 3 more Smart Citations
“…This inconsistency often leads to large variances in reported break rates amongst utilities. For example, O'Day (1982) reported that some systems such as New York City report only main breaks whereas as others such as Houston report both breaks and leaks.…”
Section: Distinction Between Pipe Breaks and Leaksmentioning
confidence: 99%
“…The primary distinction between breaks and leaks is that breaks represent a structural failure in the pipe, whereas leaks occur when either joints or service connections are not tight (O'Day, 1982). Pipe breaks occur when the culmination of loading events (internal pressure, earth loads, etc.)…”
Section: Distinction Between Pipe Breaks and Leaksmentioning
confidence: 99%
See 2 more Smart Citations
“…하지만 상수관망의 신뢰도를 정의할 수 있다하더라 도, 정의된 신뢰도를 정량화는 것은 쉽지 않은 문제이 다. Mays (1996) (Oday, 1982;Lei and Saegrov, 1998), ② 상수관의 파괴확률을 추정한 연구 (Andreou, 1986;Lei and Saegrov, 1998) (Su et al , 1987;Jowitt et al , 1993), ② 제수 밸브에 의해 격리되는 상수관과 절점을 관망의 segment 로 정의하여 피해영역 추정 (Walski, 1993(Walski, , 2002 (Goulter and Coals, 1986;Cullinane et al , 1989)의 네 가지로 구분할 수 있다. 상 수관망의 상태 평가를 위한 연구는 ① 상수관파괴로 인 한 시스템상태의 정량화 방안에 대한 연구 (Asgarpoor and Singh, 1992;Mays, 2003)와 ② 상수관망의 비정상 상태의 원인을 규정하는 연구 (Goulter and Coals, 1986;Xu et al , 1999)로 구분할 수 있다.…”
unclassified